Expression of gene encoding flavonol synthase isolating from trung du xanh tea (Camellia sinensis var. macrophylla) in E. coli - Yen, Hoang Thi Thu; Lan, Vu Thi; Thu Hue, Huynh Thi (Academia Journal of Biology, 2020)
Common flavonols in plants including quercetin, kaempferol and myricetin are synthesized from dihydroflavonols (dihydroquercetin-DHQ, dihydrokaempferol-DHK and dihydromyricetin-DHM) by flavonol synthase (FLS). In tea, FLS has been shown to metabolize dihydroquercetin to quercetin. The FLS gene was cloned and sequenced from the cultivated tea (Camellia sinensis var. macrophylla) in Thai Nguyen province. In this study, we presented the results of optimizing and designing an expression vector for recombinant FLS (recombinant FLS-rFLS). The FLS gene was ligated completely to the pET32a (+) vector, then expressed in E. coli Rosetta1 and Rosetta2 strain. Using 1mM IPTG to induce the expression of rFLS at 37oC, rFLS was obtained with 52.83 kDa in size and existed predominantly as insoluble form. E. coli Rosetta1 pET32a (+)_FLSproduces rFLS in the soluble fraction than E. coli Rosetta2 pET32a (+)_FLS. Next, E. coli Rosetta1 pET32a (+)_FLSwas optimized for expression at temperatures of 30oC, 23oC and 16oC (24 and 48 hours). After being induced for expression with 1mM IPTG in 48 hours and cultured at 16oC, E. coli Rosetta1 strain containing pET32a (+) FLS produced the largest amount of rFLS in the soluble form.